Novel Adaptive Photosynthetic Characteristics of Mesophotic Symbiotic Microalgae within the Reef-Building Coral, Stylophora pistillata - Einbinder, Shai; Gruber, David F.; Salomon, Eitan; Liran, Oded; Keren, Nir; Tchernov, Dan (Frontiers in Marine Science, 2016)
Photosynthetic coral reef structures extend from the shallow sundrenched waters to the dimly lit, “twilight” mesophotic depths. For their resident endosymbiotic dinoflagellates, primarily from the genus Symbiodinium spp., this represents a photic environment that varies ~15 fold in intensity and also differs in spectral composition. We examined photosynthesis in the scleractinian coral Stylophora pistillata in shallow (3 m) and mesophotic settings (65m) in the northern Red Sea. Symbiodinium spp. in corals originating from the mesophotic environment consistently performed below their photosynthetic compensation point and also exhibited distinct light harvesting antenna organization. In addition, the non-photochemical quenching activity of Symbiodinium spp. from mesophotic corals was shown to be considerably lower than those found in shallow corals, showing they have fewer defenses to high-light settings. Over a period of almost four years, we extensively utilized closed circuit Trimix rebreather diving to perform the study. Phylogenetic analysis showed that shallow corals (3m) transplanted to a deep reef environment (65 m) maintained their initial Symbiodinium spp. community (clade A), rather than taking on deep low-light clades (clade C), demonstrating that shallow S. pistillata acclimate to low-light mesophotic environments while maintaining their shallow photosynthetic traits. Mesophotic corals exhibited static depth-related chlorophyll content per cell, a decrease in PSI activity and enhanced sigmoidal fluorescence rise kinetics. The sigmoidal fluorescence rise kinetics we observed in mesophotic corals is an indication of energy transfer between photosynthetic units. We postulate that at mesophotic depths, a community of adapted Symbiodinium spp. utilize a unique adaptation to lower light conditions by shifting their light harvesting to a PSII based system, where PSII is structured near PSI, with additional PCP soluble antenna also trapping light that is funneled to the PSI reaction center. In this study, we provide evidence that mesophotic Symbiodinium spp. have developed novel adaptive low-light characteristics consisting of a cooperative system for excitation energy transfer between photosynthetic units that maximizes light utilization.